The chronic intestinal pseudo-obstruction subtype has prognostic significance in patients with severe gastrointestinal dysmotility related intestinal failure. Issue 6 (December 2018) - Vasant, Dipesh H.; Kalaiselvan, Ramya; Ablett, Joanne; Bond, Ashley; Abraham, Arun; Teubner, Antje; Green, Darren; Paine, Peter A.; Lal, Simon
Summary: Background & aims: Severe gastrointestinal dysmotility (GID) is a significant cause of chronic intestinal failure (CIF) with unclear benefits of sub-classifying into Chronic Intestinal Pseudo-obstruction (CIPO) and non-CIPO sub-types. We compared outcomes between CIPO and non-CIPO sub-types in a tertiary cohort of patients with CIF resulting from severe GID. Methods: Adults with primary GID, commenced on home parenteral nutrition (HPN) over a 16-year period at a national referral centre, were included. All patients satisfied GID clinical criteria which mandated evidence of small bowel involvement either objectively (abnormal antroduodenal manometry) or pragmatically (failure to progress on small bowel feeding). Clinical outcomes including HPN dependency and survival were compared between CIPO and non-CIPO sub-types. Results: Patients with primary GID requiring HPN ( n  = 45, age 38 ± 2, 33 females, 23/45 (51%) CIPO, 22/45 (49%) non-CIPO) were included. Patients with CIPO had more surgical interventions (P = 0.03), higher incidence of bacterial overgrowth (P = 0.006), greater parenteral energy (P = 0.02) and volume requirements (P = 0.05). Overall, during a mean 6 years' follow-up, 36/45 (80%) patients remained HPN dependent. Multivariate analyses confirmed that the non-CIPO sub-type (P = 0.04) and catheter related blood stream infections/1000 days (P = 0.01) were predictive factors for time to discontinuing HPN. Overall 5-year survival on HPN was 85%, with no difference between sub-types (P = 0.83). Conclusions: The CIPO sub-type is associated with higher HPN dependency and should be recognized as a separate entity in severe GID. In multidisciplinary settings with continuous close monitoring of risks and benefits, our data confirm HPN is a safe, life-preserving therapy in severe GID related CIF.